Numerical study of building heating potential from deep-buried pipes under dynamic loads: A case study of Xi'an, China - Chao Jiang; Chao Li; Xiaogang Zhang; Jinxing Ma; Jiachen Wang; Jiale Wu (Case Studies in Thermal Engineering)
The utilization of geothermal energy through deep ground heat exchangers (DGHE) primarily serves building heating purposes, posing challenges in understanding the heat transfer characteristic of buried pipes under dynamic loads. Based on practical DGHE engineering in Xi'an, China, this study establishes a three-dimensional full-size numerical model coupling the inside and outside of the pipes. It examines the heat transfer properties of DGHE when subjected to varying dynamic thermal loads and investigates how they change with different dynamic load clipping rates. A novel assessment approach for determining the heating capacity of DGHE systems in buildings is introduced. The study demonstrates a direct correlation between the building heating area (A) and the minimum inlet water temperature (Tin-Min) during the DGHE heating phase. It identifies an optimal dynamic load peak-clipping rate of around 40 %. Once this rate is set, the heating potential of DGHE in specific geological conditions, ground temperatures, and pipe sizes can be forecasted using the relationship between Tin-Min and A. This research offers valuable insights for predicting the heating potential of DGHE, aiding in the scientific planning and execution of relevant engineering projects.